What Matters in Households' Inflation Expectations? - Philippe Andrade; Erwan Gautier; Eric Mengus (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We provide survey evidence on how households' inflation expectations matter for their spending highlighting a behavioral distortion compared to the New Keynesian setup. A large share of households expects prices to remain stable instead of increasing. Such a belief is linked to individual experience with non-durable goods frequently purchased. Households expecting stable prices consume less durable goods than those expecting positive inflation. In contrast, differences across households expecting positive inflation are associated with insignificant differences in durable consumption decisions. That distortion implies that managing aggregate demand through households' inflation expectations is limited and can run out of ammunition.
Keywords: D12; D83; E21; E31; E52; 330; behavioural macroeconomics; heterogeneous beliefs; expectation formation; households' spending; inflation expectation channel; stabilization policies